Monetary policy effects on financial intermediation via the regulated and the shadow banking systems - Falk Mazelis (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We extend the monetary DSGE model by Gertler and Karadi (2011) with a non-bank financial intermediary to investigate the impact of monetary policy shocks on aggregate loan supply. We distinguish between bank and non-bank intermediaries based on the liquidity of their credit claims. While banks can endogenously create deposits to fund rm loans, non-banks have to raise deposits on the funding market to function as intermediaries. The funding market is modeled via search and matching by non-banks for available deposits of households. Because deposit creation responds to economy-wide productivity automatically, bank reaction to shocks corresponds to the balance sheet channel. Non-banks are constrained by the available deposits and their behavior is better explained by the lending channel. The two credit channels are affcted differently following a monetary policy shock. As a result of these counteracting effects, an increasing non-bank sector leads to a reduced reaction of aggregate loan supply following a monetary policy shock, which is consistent with the data. An extension to deposit like-issuance by the non-bank sector will allow further studies of re-regulating the non-bank sector.
Keywords: E32; E44; E51; G20; 330; Shadow Banking; Monetary Transmission Mechanism; Credit Channel